Gastric Dieulafoy lesion as a cause of upper gastro-intestinal bleeding in a 4-year-old child: a case report (BIRDEM Medical Journal, 2023)
Dieulafoy lesion, although rare, is a significant gastrointestinal condition that can affect children. These quiescent lesions can easily be overlooked and bleeding lesions are occasionally misidentified on endoscopy. So, accurate diagnosis depends on increased knowledge and improvements in endoscopic procedures. Treatment of Dieulafoy lesion in children usually involves in different modalities of endoscopic interventions to stop the bleeding and promote healing. In more severe cases or when endoscopic treatments are unsuccessful, surgical intervention may be required to remove the lesion. In this case report, we present the case of a boy of 4 years and 4 months old, who presented with hematemesis with melena. He appeared mildly pale, moderately dehydrated, had a moderate pulse volume, prolonged capillary refill time, a narrow pulse pressure and tenderness in the epigastrium when the abdomen was examined. His tests showed a low hemoglobin level (7.5 g/dl), a normal coagulation profile and several bleeding sites in the fundus and upper part of stomach on endoscopic examination, which are consistent with Dieulafoy lesions.BIRDEM Med J 2023; 13(3): 163-166